The Effectiveness of Employing Cognitive Trips and Geographic Atlas electronically on the Fourth –Stage- Students’ Achievement of Geography - Mohan Abbood, Ali; Shakir Abd, Al-Hareth (Opción, 2019)
The objective of the current research is to find out the effectiveness of employing cognitive trips and geographic Atlas in the assimilation of geography among n fourth – secondary stage students. In order to know the results of the research, the researchers have formulated the following zero hypothesis: (There is no sta- tistically significant difference between (0,05). The first three groups are the first experimental group to study geophysics in electronic cognitive trips and the sec- ond experimental group which is taught electronically by the atlas and the control group which studies the same subject in the usual way in the post-achievement test. (90) students have been distributed in three divisions, and was followed by the experimental research methodology with a post-design of three equal groups. The research tool is the test of the achievement of the dimension, which was damaged from (40) test paragraph of the type of multiple choice, after the truth was extracted by experts . The results of the study, after statistical analysis, it has showed that Schiffe’s tests of bilateral dimension comparisons were higher than those of the two experimental groups in the control group. The researchers have concluded that cognitive trips and geographic atlases are effective teaching methods in increasing the level of im- munization For the fourth-stage students / literary in geography. Moreover, the su- periority of the students of the two experimental groups is attributed to the students who studied in the usual way for these two teaching methods of the effectiveness of educational science in stimulating the love of the subject and to stimulate mental and self-activity among the fourth grade students. The researchers recommend the adoption of cognitive trips and atlases that have been adopted electronically in the teaching of geography. In addition to the current research, the researchers propose similar study be conducted on another study stage.